Wireless water level detection system - Mat Toridi, Noorellimia; Amri, Muhammad Idham Haiqal; Mohd Hisham, Muhammad Shamir Sadiq; Ismail, Nur Shafiqah; Kupo, Anelka Dau; Mohamed Ramli, Norulhuda; Khairudin, Nurulhuda; Abd Aziz, Samsuzana (Malaysian Society of Agricultural and Food Engineers, 2024)
The irrigation system is crucial in ensuring that each field receives the necessary water supply to meet the crops' demands. It is essential to ensure that the water flow is consistent and uninterrupted and that the water levels are monitored and controlled. Therefore, this paper designs a wireless water level detection system that works automatically by reading the height of the water level using an ultrasonic sensor. Then, the water level data is sent to an applicationso that the users can monitor the height of the water in real-time. This system was designed using two main components: an HC-SR04 ultrasonic sensor and a NodeMCU microcontroller. The HC-SR04 periodically transmits data on the water level in real time, and then the NodeMCU uploads this datato the monitoring platform. Finally, the wireless water level detection system is tested in a laboratory environment. A solid linear regression was obtained between the measured and actual water level height (R2=0.99).